2018
DOI: 10.1051/shsconf/20184801025
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of problem solving proficiencies with self-efficacy perceptions of students in faculty of health sciences of cyprus international university

Abstract: The aim of this study is to evaluate the self-efficacy perceptions and problem solving competencies of students of Health Sciences Faculty. The study included 150 students studying in 4th grade who completed the questionnaire completely. Self-efficacy-competence scale was used to evaluate students’ self-efficacy perceptions, and Problem Solving Inventory was used to evaluate problem solving proficiencies. The mean age of the students included in the study was 22.26 ± 1.27 years and 59.3% [n = 89] were female s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Such efficacy test even displays its effect on the inverse GPS. In connection with that type, Cetin et al (2018) corroborated there is a negative significant correlation between self-efficacy and problem solving, and Lishinski et al (2016) reported that there is reciprocal effect between performance for mathematics and self-efficacy. Factually, it is right to say that being able to solve problems shall influence student self-efficacy capacity.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Such efficacy test even displays its effect on the inverse GPS. In connection with that type, Cetin et al (2018) corroborated there is a negative significant correlation between self-efficacy and problem solving, and Lishinski et al (2016) reported that there is reciprocal effect between performance for mathematics and self-efficacy. Factually, it is right to say that being able to solve problems shall influence student self-efficacy capacity.…”
Section: Discussionmentioning
confidence: 81%
“…The constructs are self-efficacy aspects as specific domain of motivation (Zhang, 2017a). Notwithstanding, there is no self-efficacy to result in competence unless students have required skill to succeed (Cetin et al, 2018). With this basis, the researchers continued the effect analysis of BGC and two MSE models on GPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study result is unsupported by Cetin et al (2018) study. The aim of that study was to assess self-efficacy and problem solving competencies of students of Health Sciences Faculty.…”
Section: Discussionmentioning
confidence: 95%